The freedom of histories : reassessessing Grotius on the sea - G. Edmond (Law Text Culture, 1995)
You might think it was obvious that Hugo Grotius was a man of his age. Yet the majority of historical accounts have failed to consider his work as the product of a life lived during a particular epoch. Instead historians have tended to particularise, through extraction and emphasis, various claims seemingly apparent in his work. In so doing they have created sanitised and deformed interpretations which fail to render substantive coherence to the whole of his work. The work has been described as the inauguration of a matured conceptualisation of international law and relations reflecting modem perceptions. Such analysis fails to adequately explain the coexistence, within the work, of both archaic and modem conceptions. Antiquated or accretious components have been glossed over or ignored. This has been the case for the majority of interpreters of Mare Liberum. With the infusion of new assumptions about historical methodology, texts are less likely to be conceived in vacuo. No longer can historians invoke a parthenogenetic explanation for knowledge claims. Rather the historian's role has shifted to include the consideration of more sociological and contextual influences in unravelling the history of ideas. These techniques involve an attempt to render historical texts as coherent and rational, but by the standards of argument and rationality available at the time of their construction, as understood by modem historians.